Diabetic Lipoproteins and Adrenal Aldosterone Synthesis – A Possible Pathophysiological Link? - Saha, S.; Willenberg, H. S.; Bornstein, S. R.; Graessler, J.; Kopprasch, S. (Hormone and Metabolic Research, 2012)
An increased prevalence of diabetes mellitus (DM) has been reported in patients with primary aldosteronism (PA). DM is associated with abnormal structure and metabolism of circulating lipoproteins, which normally serve as a major source of cholesterol for adrenocortical steroidogenesis. The present study has been designed to investigate the effect of diabetically modified lipoproteins on adrenocortical aldosterone synthesis. Lipoproteins (VLDL, LDL, HDL) isolated from healthy volunteers, were subjected to oxidation or glycoxidation in the presence of sodium hypochlorite (3 mmol/l) or glucose (200 mmol/l), and aldosterone synthesis in human adrenocortical cells (H295R) was examined. Native and glycoxidized VLDL had greatest stimulatory effect on aldosterone production by 15-fold and 14-fold, respectively. At the molecular level, these VLDL produced maximum increases in Cyp11B2 mRNA level up to 17-fold. Experiments with the highly selective scavenger receptor class B type I (SR-BI) inhibitor BLT-1 revealed that cholesterol uptake from native and glycoxidized HDL and VLDL for hormone production is considerably mediated by SR-BI. Western blot analysis of extracellular signal-regulated kinase (ERK 1/2) phosphorylation and experiments with the MEK inhibitor U0126 indicated a specific mechanistic role of the ERK cascade in lipoprotein-mediated steroid hormone release. In summary, diabetic dyslipidemia and modification of circulating lipoproteins may promote adrenocortical aldosterone synthesis.
Keywords: glycoxidation; oxidation; adrenocortical cells; scavenger receptor; extracellular signal-regulated kinase